2010
DOI: 10.1002/jssc.201000429
|View full text |Cite
|
Sign up to set email alerts
|

Improving the knowledge on Piper betle: Targeted metabolite analysis and effect on acetylcholinesterase

Abstract: Piper betle is a species growing in South East Asia, where its leaves are economically and medicinally important. To screen the highest possible number of volatile and semivolatile components, the leaves were subjected to headspace solid-phase microextraction, hydrodistillation and Soxhlet extraction, prior to analysis by GC/MS. Fifty compounds (identified by comparison with standard compounds or tentatively by National Institute of Standards and Technology database) were determined, 23 being described for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Essential oils (Bajpai, Sharma, Kumar, & Madhusudanan, ; Jirovetz, Puschmann, Buchbauer, & Muhammad, ; Karak et al, ; Kumar et al, ; Saxena, Khare, Saxena, Syamsundar, & Srivastava, ; Suryasnata, Sandeep, Parida, Nayak, & Mohanty, ) and some important phenols, for example, hydroxychavicol and its acetate form (Ali et al, ; Amonkar, Nagabhusan, D’Souza, & Bhide, ; Pin et al, ) were reported from the leaves of P. betle . Some other non‐volatile components, for example, amino acids, sugars, organic acids, polyols, fatty acids, terpenes, and phenolic compounds have also been reported previously (Karak, Bhattacharya, Nandy, Saha, & De, ; Valentão et al, ) from P . betle leaves.…”
Section: Introductionsupporting
confidence: 69%
“…Essential oils (Bajpai, Sharma, Kumar, & Madhusudanan, ; Jirovetz, Puschmann, Buchbauer, & Muhammad, ; Karak et al, ; Kumar et al, ; Saxena, Khare, Saxena, Syamsundar, & Srivastava, ; Suryasnata, Sandeep, Parida, Nayak, & Mohanty, ) and some important phenols, for example, hydroxychavicol and its acetate form (Ali et al, ; Amonkar, Nagabhusan, D’Souza, & Bhide, ; Pin et al, ) were reported from the leaves of P. betle . Some other non‐volatile components, for example, amino acids, sugars, organic acids, polyols, fatty acids, terpenes, and phenolic compounds have also been reported previously (Karak, Bhattacharya, Nandy, Saha, & De, ; Valentão et al, ) from P . betle leaves.…”
Section: Introductionsupporting
confidence: 69%
“…The Piper betel leaf is used in folk medicine for treatment of several situations [72], and the leaf extracts are experimentally shown to be useful as antimicrobial [73], anti-leishmanial [74], antimalarial [75], anti-filarial [76], anti-fungal [77], anti-allergic [78], immunomodulator [79], gastroprotective [80], antioxidant [81], and anti-inflammatory [82] agents. We performed literature mining and collected 128 active phytochemicals from betel leaf and used them to screen against these two targets.…”
Section: Resultsmentioning
confidence: 99%
“…Given that it is a cheap and readily accessible natural product, various parts of the Piper betel plant especially betel leaves, are used in traditional medicine for treatment of several conditions such as abscesses, constipation, conjunctivitis, itches, rheumatism, abrasions, and many more (14,15). Although the roots of Piper betel have served as alternative oral contraceptives, the oil obtained from betel leaves has bactericidal action (13).…”
Section: Some Plants Have It All: the Versatile Pharmacopoeia Of Pipementioning
confidence: 99%